Analisis Hukum Terhadap Tata kelola Alokasi Dana Desa Dalam Meningkatkan Kesejahteraan Masyarakat Desa Palippu - Mallarangeng, Andi Bau; Rahayu, Sri; Armelia, Nurul; Muharram, Ahmad Akhmar; Fajar, Baso Rahmat; Yunus, Muh Anugrah; Mutmainna (Legal Journal of Law, 2024)
One of the most important ways for villages to implement programs to improve community welfare is through the provision of village funds. Compared to district governments, which certainly have broader and more complex problems, it is believed that village governments are better able to identify the most important community needs. This study aims to determine the management of village fund allocations as well as the factors that influence the management of village funds in an effort to improve the welfare of the community of Palippu Village, which is located in Tanasitolo District, Wajo Regency. This study employs a descriptive qualitative methodology and is classified as field research, which includes observation, interview, and documentation. Firstly, this study found that the ADD management process includes planning, implementation, reporting, accountability and monitoring. The Palippu village government, in the Tanasitolo sub-district, Wajo Regency, manages ADD according to the technical guidelines stipulated in the laws and regulations. However, the process is still not optimal. Second, village fund management is influenced by supporting and inhibiting factors. Community participation, facilities, and infrastructure are supporting factors, and human resources, communication, and technical guidelines for managing ADD change every year.